3D Modeling of of Distribution Andesite and Breccia Rocks Using Geoelectric Resistivity in Potential Areas of Minerals in Madiun Regency, Indonesia - Rizqi Prastowo; Setyo Pambudi; Al Hussein Flowers Rizqi; Vico Luthfi Ipmawan; Dyah Arum Arimurti; Berwyn Dzaky Radhitya (International Journal of Hydrological and Environmental for Sustainability, 2024)
This research focuses on the distribution of andesite and breccia rocks in East Java, Indonesia, specifically in Morang Village, Madiun Regency, through geoelectric resistivity measurements. This study aims to enhance geoelectric interpretation from 2D to 3D, providing high accuracy in target positioning for potential building material resources. By employing a dipole-dipole configuration with electrode spacing, the resistivity values of subsurface rocks were analyzed to classify the types and distributions of building materials, such as andesite and breccia. Data was collected through field measurements and geological surveys, followed by inverse modeling using the least squares method. The results reveal that andesite, with resistivity values above 1000 Ωm, is distributed predominantly in the southeast-northwest trend at a depth of 10–15 meters, while breccia, with resistivity values between 600–900 Ωm, is found at various depths closer to the surface. The geological interpretation suggests that the southeast-northwest orientation may correlate with an ancient basin structure, which directed lava flow during past volcanic activities, forming these rock layers. This study contributes valuable information for local infrastructure planning by providing data on accessible rock resources essential for construction. The application of the 3D geoelectric model offers an effective tool for environmental assessment and mineral exploration, promoting sustainable resource management.